Study of Crumb Rubber as Binder Material in Asphalt - SOI LEE CHIA; MOHD ZAMRI JAMALUDIN; ABDUL MUIZ ABD RAJAK HAMIM (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2023)
Asphalt is a mixture of aggregates, bitumen, quarry dust, and cement. As an addition in hot mix asphalt mixtures, recycled tire rubber known as